Mine elevator friction liner made of novel composite material and production process of mine elevator friction liner
By using bisphenol A cyanate ester resin-based composite material in the friction lining of a mine hoist, and utilizing a sequential thermal energy buffering and catalytic in-situ film formation system, a high thermal stability friction film is generated, solving the problems of thermal degradation of friction performance and wire rope wear, and achieving stable friction and low wear at high temperatures.
Patent Information
- Application Number
- CN202511546510.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2025-12-16
AI Technical Summary
The friction pads of mine hoists suffer from thermal degradation of friction performance, accelerated wear, and excessive wear on wire ropes due to the sharp increase in friction interface temperature under heavy load, high speed, and high frequency braking conditions.
A composite material containing bisphenol A cyanate ester resin as the matrix is used, combined with a sequential thermal energy buffer system and a catalytic in-situ film formation system. Through the stepwise heat absorption of zinc stearate and calcium stearate, a highly thermally stable inorganic salt glassy friction film is generated, which isolates the matrix from the paired steel wire rope and forms a stable friction interface.
It maintains a stable coefficient of friction at high temperatures, has an extremely low thermal decay rate and a high recovery rate, reduces material wear, protects the wire rope from wear, and extends its service life.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of friction material technology, specifically to a friction liner for a mine hoist made of a novel composite material and its manufacturing process. Background Technology
[0002] Mining hoists are core equipment in vertical transportation systems in coal mines, metal mines, and other similar facilities. Their friction linings, as key components for precise braking and safe operation, directly determine the hoist's safety, reliability, and operational efficiency. For a long time, existing mining hoist friction linings have generally adopted phenolic resin-based composite material systems, supplemented with various reinforcing fibers (such as aramid and glass fiber) and fillers.
[0003] However, under harsh operating conditions such as heavy loads, high speeds, and high-frequency braking in mine hoists, a large amount of heat is generated at the friction interface, causing a sharp rise in temperature. Under continuous high temperatures, the phenolic resin matrix is prone to irreversible reactions such as thermal decomposition and oxidative degradation, resulting in significant fluctuations in the friction coefficient of the friction pads, and even a sharp decline in thermal degradation. This thermal degradation leads to unstable braking performance, thereby affecting the operating accuracy and safety of the hoist.
[0004] Furthermore, in high-temperature and high-pressure friction environments, the material wear of existing friction pads is usually quite severe, and their insufficient wear resistance leads to a high wear rate. The rapid consumption of pad material not only shortens its own service life and increases the frequency of maintenance and replacement, but also further exacerbates the instability of the friction interface and heat accumulation due to the generation of wear debris and the deterioration of material properties.
[0005] More importantly, some hard particles or high-temperature abrasive debris in traditional friction pads can cause significant wear to the metal mating parts (especially the wire ropes of mine hoists) during friction. This excessive wear of the wire ropes often accelerates fatigue damage, reduces the load-bearing capacity and service life of the wire ropes, and seriously threatens the safety of mine production. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the problems of thermal degradation of friction performance, accelerated wear, and excessive wear of wire rope caused by the sharp increase in friction interface temperature of existing mine hoist friction pads under heavy load, high speed and high frequency braking conditions.
[0007] In a first aspect, the present invention provides a novel composite material for a mine hoist friction liner, which is made from raw materials comprising the following parts by weight: Matrix resin: 30-45 parts; Blended reinforced fiber system: 35-50 parts; Sequential thermal energy buffering system: 3-8 parts; Catalytic in-situ film formation system: 4-13 parts; Basic friction performance modifier: 4-10 parts; The matrix resin is a bisphenol A cyanate resin.
[0008] By employing the above technical solution, this invention constructs a multifunctional synergistic composite material system. Bisphenol A cyanate resin serves as the matrix, and its cured product exhibits a high glass transition temperature, low dielectric constant, high dimensional stability, and excellent hydrothermal properties, providing a fundamental guarantee for maintaining the mechanical integrity of the friction pad at high temperatures. Based on this, this invention introduces a sequential thermal energy buffering system and a catalytic in-situ film-forming system, which can actively regulate interfacial heat flow and generate a protective friction film in situ during friction. The mechanism of action is as follows: The sequential thermal buffering stage: When the friction interface temperature begins to rise due to braking, the sequential thermal buffering system responds first. The components with lower melting points (such as zinc stearate, with a melting point of approximately 120-130°C) undergo a melting phase transition first, absorbing the frictional heat of the first stage and forming a first-level thermal buffer platform, effectively suppressing the rapid rise in interface temperature. If the braking conditions are severe and the interface temperature continues to rise, the components with higher melting points (such as calcium stearate, with a melting point of approximately 150-160°C) continue to undergo a melting phase transition, absorbing the heat of the second stage and forming a second-level thermal buffer platform. This stepwise energy absorption mechanism smooths out the instantaneous temperature rise over a wide temperature range, providing protection for the matrix resin and creating stable temperature conditions for the subsequent formation of the friction film.
[0009] Catalytic in-situ film formation stage: Within the stable high-temperature window created by the aforementioned thermal buffering effect, the catalytic in-situ film formation system is activated. The surface-treated attapulgite clay in the system exhibits catalytic activity due to the exposure of more surface active sites after treatment. Under this catalytic action, submicron-sized antimony trioxide and nano-sized silica in the system undergo a series of complex physicochemical reactions with wear particles (mainly iron oxides) from the paired steel wire rope and molten metal stearates. These reactions generate a dense, stable inorganic salt glassy friction film in situ at the friction interface, mainly composed of metal antimonates and silicates.
[0010] The friction film adheres firmly to the pad surface, effectively isolating the matrix resin from the paired steel wire rope. This transforms the friction behavior from direct contact between the composite matrix and the metal into shearing between the friction films. The friction film exhibits high thermal stability and high-temperature self-lubricating properties, thus maintaining a stable coefficient of friction at high temperatures and significantly reducing material wear.
[0011] In summary, by using the time-sequential synergistic effect of thermal energy buffering and in-situ film formation, this invention fundamentally solves the problem of thermal runaway at the friction interface, constructs a dynamically stable high-temperature protection structure, and thus achieves excellent high-temperature friction performance, extremely low thermal decay rate, high recovery rate, long life, and low aggression to steel wire ropes.
[0012] Preferably, the hybrid reinforcing fiber system is composed of basalt fiber and aramid fiber, wherein the amount of basalt fiber is 26.6-35 parts and the amount of aramid fiber is 8.4-15 parts.
[0013] By employing the above technical solution, basalt fiber, possessing high strength, high modulus, and excellent high-temperature resistance, serves as a rigid skeleton to bear the main load; aramid fiber, with its high toughness, wear resistance, and low density, acts as a tough skeleton to absorb impact energy and improve the material's resistance to abrasive wear. The combined use of these two materials forms a reinforced network that combines rigidity and toughness, endowing the friction pad with high strength, high impact toughness, and dimensional stability.
[0014] Preferably, the sequential thermal energy buffer system is composed of zinc stearate and calcium stearate, wherein the mass ratio of zinc stearate to calcium stearate is 1:1 to 3:1.
[0015] By adopting the above technical solution, and utilizing the difference in melting points between zinc stearate and calcium stearate (approximately 125℃ and 155℃ respectively), a stepped heat absorption platform was constructed, realizing the time-sequential and phased management of frictional heat flow, thereby improving the efficiency and expanding the range of heat regulation.
[0016] Preferably, the catalytic in-situ film-forming system consists of antimony trioxide, silicon dioxide, and surface-treated attapulgite clay, with a total dosage of 4-13 parts.
[0017] By adopting the above technical solution, antimony trioxide is the key precursor for forming a high-temperature stable friction film (metal antimonate), nano-silica serves as a structural filler and reinforcing phase in the film formation process, and surface-treated attapulgite clay provides a catalytic center and structural support for the film formation reaction. The synergistic effect of the three ensures the rapid and stable formation of a high-temperature protective friction film.
[0018] Preferably, the particle size of the acid-treated attapulgite clay is no greater than 38 μm.
[0019] By adopting the above technical solution, it is ensured that attapulgite clay, as a carrier for catalytic in-situ film formation system, has excellent dispersibility and flowability. Its fine particle size can be uniformly distributed between the resin matrix and fibers, improving the spreading uniformity and reaction efficiency of the transfer membrane precursor at the friction interface.
[0020] Secondly, the present invention provides a manufacturing process for friction linings of mine hoists made of novel composite materials, comprising the following steps: (a) The components of the catalytic in-situ film formation system are dispersed in the solvent of bisphenol A cyanate resin to form a functional suspension; (b) The components of the sequential thermal energy buffer system are mixed with the components of the basic friction performance modifier to obtain low-temperature functional powder; (c) The hybrid reinforcing fiber system is impregnated in the functional suspension and pre-dried to obtain a resin prepreg; (d) The resin prepreg is stacked and the low-temperature functional powder is spread between the layers to obtain a blank; (e) The blank is subjected to programmed heating and curing to obtain a friction pad.
[0021] By adopting the above technical solution, this process ensures the precise positioning of each functional component in the microstructure of the composite material through unique material distribution and processing path, thereby maximizing their synergistic effect.
[0022] First, in step (a), submicron and nano-sized inorganic particles in the catalytic in-situ film-forming system are pre-dispersed uniformly in liquid resin using methods such as ultrasound. This step solves the technical problem of easy agglomeration of micro / nano fillers in viscous matrices, ensuring that the catalytic active sites and micro-reinforcing phases are uniformly distributed throughout the matrix, laying the structural foundation for the subsequent formation of a uniform and dense friction film.
[0023] Secondly, step (b) prepares the low-melting-point heat buffer component and solid lubricant into separate dry powders. This design avoids adverse reactions or premature melting of these components with the resin solvent during the wet impregnation process, thus preserving their original physicochemical properties.
[0024] The most crucial step is the interlayer spreading process in step (d). Instead of simply mixing all components as a whole, it constructs functional interface layers rich in thermal management and lubricating components between the layers of the reinforcing fiber prepreg. This unique layered structure allows thermal buffering and lubrication to occur most preferentially and directly on the potential shear surfaces within the material during friction, maximizing functional utilization.
[0025] Finally, the programmed temperature curing process in step (e) ensures the complete curing of the high-performance cyanate ester resin and the dense, defect-free interior of the material by first applying the resin at low temperature and low pressure and then curing it at high temperature and high pressure. This process ultimately yields a friction pad with a specific micro-region functional distribution and excellent overall performance.
[0026] Preferably, before step (a), the method further includes the step of preparing the surface acid-treated attapulgite clay: adding attapulgite clay powder to a sulfuric acid solution with a concentration of 2-5 mol / L, stirring and reacting at 80-95°C for 2-6 hours, followed by filtration, washing and drying.
[0027] By adopting the above technical solution, the activation treatment of attapulgite clay is incorporated into the process flow as a pre-process step, ensuring the activity of the core components of the catalytic in-situ film formation system.
[0028] Preferably, step (d) is specifically carried out as follows: the resin prepreg is cut and layered, and between every two layers of prepreg, a layer of the low-temperature functional powder is evenly spread using an electrostatic or vibrating sieving device, with a spreading amount of 50-150 g / m³. 2 .
[0029] By adopting the above technical solution, using precise spreading equipment and controlling the spreading amount per unit area, the thickness of the functional interface layer and the concentration of components are precisely controlled, ensuring the performance stability and consistency between product batches.
[0030] Preferably, in step (e), the process parameters for programmed temperature rise curing are as follows: first, under a pressure of 0.5-1.5 MPa, the temperature is raised to 80-100℃ and held for 45-75 minutes; then the pressure is increased to 10-20 MPa, and the temperature is raised to 180-200℃ at a rate of 1-3℃ / min, and the pressure and temperature are held for 90-150 minutes.
[0031] By adopting the above technical solution, the two-stage curing process curve is optimized for the compatibility of the cyanate ester resin system and the multifunctional filler system in this invention. The low-temperature platform in the first stage ensures sufficient resin flow and wetting, effectively eliminates volatiles, and avoids the formation of pores inside the product; the high-temperature and high-pressure platform in the second stage ensures that the triazine ring crosslinking reaction of the cyanate ester resin can proceed fully, forming a network structure with high crosslinking density, thereby endowing the material with high thermal stability and high mechanical strength.
[0032] Preferably, after step (e), a high-temperature post-treatment step is further included: the demolded product is kept at 215-230°C for 120-240 minutes.
[0033] By adopting the above technical solution, high-temperature post-treatment of cured products can eliminate the internal stress generated during the curing process and allow unreacted functional groups in the resin matrix to continue to react, thereby further improving the crosslinking density and glass transition temperature of the material and maximizing the dimensional stability and mechanical property retention rate of the material at high temperatures.
[0034] This invention provides a novel composite material friction liner for mine hoists and its manufacturing process. It offers the following advantages: 1. This invention provides a sequential thermal energy buffering system and a catalytic in-situ film formation system. The sequential thermal energy buffering system utilizes the different melting points of zinc stearate and calcium stearate to absorb and buffer the instantaneous high heat generated by friction in a stepwise manner, suppressing the sharp rise in interface temperature. On this basis, the catalytic in-situ film formation system is activated to generate a layer of highly thermally stable inorganic salt glassy friction film at the friction interface. This friction film effectively isolates the resin matrix, thereby maintaining a stable coefficient of friction at high temperatures, with an extremely low thermal decay rate and a high recovery rate.
[0035] 2. During use, the protective friction film generated by the catalytic in-situ film-forming system of the present invention becomes the actual load-bearing and shear interface, effectively protecting the underlying cyanate ester resin matrix and hybrid reinforcing fibers from direct wear. This mechanism, which primarily restricts wear to the dynamically self-healing friction film, changes the material's wear pattern, resulting in a volumetric wear rate far lower than that of traditional materials that rely on the matrix and fibers themselves to resist wear.
[0036] 3. The friction film generated by the friction pad of the present invention during the friction process not only adheres to the surface of the pad, but can also be partially transferred and firmly adhered to the surface of the paired steel wire rope. This changes the friction interface from direct contact between the composite material and the steel wire rope to contact between friction films, reducing abrasive wear and adhesive wear effects on the steel wire rope, and reducing mass loss and surface damage of the steel wire rope. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the scope of protection of the invention.
[0038] Preparation Example 1: In a 1000 mL three-necked flask equipped with a mechanical stirrer and thermometer, 500 g of a 4 mol / L sulfuric acid solution was added, and the mixture was heated to 90 °C. While stirring (200 rpm), 100 g of attapulgite clay powder that had passed through a 400-mesh sieve was slowly added, and the reaction was continued at 90 °C for 4 hours. After the reaction was complete, heating was stopped, and the mixture was filtered under reduced pressure. The resulting filter cake was repeatedly washed with deionized water until the pH of the washing effluent was neutral (pH 6.5-7.5). The washed filter cake was then placed in a 110 °C forced-air drying oven and dried for 8 hours until constant weight. The dried lumps were removed, pulverized using an air jet mill, and collected through a 400-mesh sieve to obtain the surface-acid-treated attapulgite clay product.
[0039] Preparation Example 2: In a 1000 mL three-necked flask equipped with a mechanical stirrer and thermometer, 500 g of a 2 mol / L sulfuric acid solution was added, and the mixture was heated to 80 °C. While stirring (150 rpm), 100 g of attapulgite clay powder that had passed through a 400-mesh sieve was slowly added. The reaction was continued at 80 °C with stirring for 2 hours. After the reaction was complete, the subsequent filtration, washing, drying, and pulverizing steps were the same as in Preparation Example 1, yielding the surface-acid-treated attapulgite clay product.
[0040] Preparation Example 3: In a 2000 mL three-necked flask equipped with a mechanical stirrer and thermometer, 1000 g of a 5 mol / L sulfuric acid solution was added, and the mixture was heated to 95 °C. While stirring (300 rpm), 100 g of attapulgite clay powder that had passed through a 400-mesh sieve was slowly added. The reaction was continued at 95 °C with stirring for 6 hours. After the reaction was complete, the subsequent filtration, washing, drying, and pulverizing steps were the same as in Preparation Example 1, yielding the surface-acid-treated attapulgite clay product.
[0041] Examples 1-4: Example 1: This embodiment provides a novel composite material friction liner for a mine hoist and its manufacturing process. The mass proportions of each component in the formula are as follows: 38 parts of bisphenol A type cyanate resin (matrix resin); The hybrid reinforcing fiber system consists of 42 parts, comprising 29.5 parts basalt fiber and 12.5 parts aramid fiber; Five portions of a sequential thermal energy buffer system; Eight parts of the catalytic in-situ film formation system; The sequential thermal energy buffering system consists of zinc stearate and calcium stearate, each in 2.5 parts; The catalytic in-situ film formation system consists of antimony trioxide, silicon dioxide and attapulgite clay from Preparation Example 1, with 4 parts, 3 parts and 1 part respectively. The basic friction performance modifier consists of 7 parts, which are composed of 3.5 parts of flake graphite and 3.5 parts of hexagonal boron nitride.
[0042] Its preparation method includes the following steps: (1) Preparation of functional suspension: 38 parts of bisphenol A cyanate resin were dissolved in 50 parts of acetone to prepare a resin solution. 4 parts of antimony trioxide, 3 parts of silicon dioxide and 1 part of surface-treated attapulgite clay from Preparation Example 1 were added to the solution. The solution was then treated at 30°C using an ultrasonic dispersion device with a frequency of 30 kHz for 60 minutes to obtain the functional suspension.
[0043] (2) Pre-impregnation of hybrid fibers: 29.5 parts of basalt fiber and 12.5 parts of aramid fiber were uniformly mixed to form a fiber cloth, which was then passed through an impregnation tank at a speed of 3 m / min to fully impregnate the functional suspension prepared in step (1). The cloth was then pre-dried in an 80°C drying tunnel under the control of a scraper roller to obtain a prepreg with a resin content of 50 wt%.
[0044] (3) Preparation of low-temperature functional powder: Under the conditions of ambient temperature of 30℃ and relative humidity of 40%, 2.5 parts of zinc stearate, 2.5 parts of calcium stearate, 3.5 parts of flake graphite and 3.5 parts of hexagonal boron nitride were placed in a V-type mixer and mixed at a speed of 30 rpm for 90 minutes to obtain low-temperature functional powder.
[0045] (4) Lamination and Layering: The prepreg obtained in step (2) is cut into the required specifications and laminated. Between every two layers of prepreg, a layer of low-temperature functional powder prepared in step (3) is evenly spread using a vibrating sieve device, with a spreading amount of 100g / m². 2 .
[0046] (5) Programmed temperature rise curing and molding: The stacked blanks are transferred into a hot press mold. A pressure of 1.0 MPa is applied, the temperature is raised to 90°C and held for 60 minutes. Then the pressure is increased to 15 MPa, and the temperature is raised to 190°C at a rate of 2°C / min, and the pressure and temperature are held for 120 minutes. Under the pressure, the temperature is lowered to below 60°C at a rate of 4°C / min, and the pressure is released and the mold is demolded. The product is placed in an oven, heated to 220°C at a rate of 3°C / min, held for 180 minutes, and then naturally cooled to room temperature in the oven to obtain the final friction pad product.
[0047] Example 2: This embodiment provides a novel composite material friction liner for a mine hoist and its manufacturing process. The mass proportions of each component in the formula are as follows: 33 parts of bisphenol A cyanate resin (matrix resin); The hybrid reinforced fiber system consists of 38 parts, comprising 26.6 parts basalt fiber and 11.4 parts aramid fiber; Eight portions of a sequential thermal energy buffer system; 12 parts of the catalytic in-situ film formation system; The sequential thermal energy buffering system consists of zinc stearate and calcium stearate, each in 4 parts; The catalytic in-situ film formation system consists of antimony trioxide, silicon dioxide, and surface acid-treated attapulgite clay from Preparation Example 1, with 6 parts, 4 parts, and 2 parts respectively. The basic friction performance modifier consists of 7 parts, which are composed of 3.5 parts of flake graphite and 3.5 parts of hexagonal boron nitride.
[0048] The preparation method is the same as in Example 1.
[0049] Example 3: This embodiment provides a novel composite material friction liner for a mine hoist and its manufacturing process. The mass proportions of each component in the formula are as follows: 38 parts of bisphenol A cyanate resin (matrix resin); The mixed reinforcing fiber system consists of 42 parts, comprising 29.5 parts basalt fiber and 12.5 parts aramid fiber; Five portions of a sequential thermal energy buffer system; Eight parts of the catalytic in-situ film formation system; The sequential thermal energy buffering system consists of zinc stearate and calcium stearate, with 3.75 parts and 1.25 parts respectively; The catalytic in-situ film formation system consists of 3 parts of antimony trioxide and silicon dioxide and 4 parts, 3 parts and 1 part of attapulgite clay from Preparation Example 1, which are respectively surface acid treated. The basic friction performance modifier consists of 7 parts, which are composed of 3.5 parts of flake graphite and 3.5 parts of hexagonal boron nitride.
[0050] The preparation method is the same as in Example 1.
[0051] Example 4: This embodiment provides a novel composite material for manufacturing friction linings for mine hoists and its production process. The mass proportions of each component in the formula are as follows: 38 parts of bisphenol A type cyanate resin (matrix resin); The hybrid reinforced fiber system consists of 42 parts, comprising 33.6 parts basalt fiber and 8.4 parts aramid fiber; Five portions of a sequential thermal energy buffer system; Eight parts of the catalytic in-situ film formation system; The sequential thermal energy buffering system consists of zinc stearate and calcium stearate, each in 2.5 parts; The catalytic in-situ film formation system consists of antimony trioxide, silicon dioxide and attapulgite clay from Preparation Example 1, with 4 parts, 3 parts and 1 part respectively. The basic friction performance modifier consists of 7 parts, which are composed of 3.5 parts of flake graphite and 3.5 parts of hexagonal boron nitride.
[0052] The preparation method is the same as in Example 1.
[0053] Comparative Examples 1-6: Comparative Example 1: This comparative example provides a friction pad using existing technology, the formulation (parts by weight) of which is: 45 parts phenolic resin; 35 parts aramid fiber; 5 parts flake graphite; and 15 parts barium sulfate. The preparation method is as follows: all components are dry-mixed uniformly in a high-speed mixer; the mixture is hot-pressed at 25 MPa and 170°C for 15 minutes; and the final product is obtained after cooling and demolding.
[0054] Comparative Example 2: Compared with Comparative Example 1, the difference is that the matrix resin was replaced by 45 parts of phenolic resin with 45 parts of bisphenol A cyanate resin, and the same programmed temperature rise curing molding process as in Example 1 was used.
[0055] Comparative Example 3: Compared with Example 1, the difference is that it does not contain zinc stearate, calcium stearate, antimony trioxide, silicon dioxide, and surface acid-treated attapulgite clay, and is replaced with 13 parts of barium sulfate, while the rest are the same.
[0056] Comparative Example 4: Compared with Example 1, the difference is that the component does not contain calcium stearate, and its 2.5 parts by mass are replaced by zinc stearate, that is, the total amount of zinc stearate added is 5 parts, and the rest are the same.
[0057] Comparative Example 5: Compared with Example 1, the difference is that the composition does not contain surface acid-treated attapulgite clay, and 1 part of its mass is replaced by silica, that is, the total amount of silica added is 4 parts, and the rest are the same.
[0058] Comparative Example 6: Compared with Example 1, the difference is that the surface acid-treated attapulgite clay from Preparation Example 1 used in the components was replaced with an equal mass of untreated attapulgite clay raw material, and all other aspects were the same.
[0059] Test Examples 1-4: Test Example 1: This test case aims to verify the thermal response characteristics of each component in a sequential thermal energy buffer system through precise thermal melting behavior analysis, in order to confirm the feasibility of its step-by-step endothermic mechanism.
[0060] Experimental methods: The thermal melting behavior of the samples was determined using a fully automated video melting point apparatus. The test samples were: zinc stearate powder, calcium stearate powder, and the sequential thermal energy buffer system (a 1:1 mass ratio compound of zinc stearate and calcium stearate) prepared in step (3) of Example 1.
[0061] The dried sample powder was packed into clean standard melting point capillaries, with a filling height of approximately 3 mm. The capillaries were then placed in the instrument's heating module. The initial temperature was set to 100℃, and heating was carried out at a linear heating rate of 1 K / min. The instrument monitored the state of the sample inside the capillary in real time using a high-resolution camera and automatically recorded the temperature range from the initial collapse (initial melting point) to the complete transformation into a transparent liquid (final melting point). Each sample was tested three times, and the results were averaged.
[0062] Experimental data: The results of the thermal melting behavior analysis of each sample are shown in Table 1.
[0063] Table 1. Analysis data on the thermal melting behavior of each component in the sequential thermal energy buffer system
[0064] Note: In Table 1 above, “—” indicates that the test sample did not observe the corresponding second melting range under the corresponding test conditions.
[0065] Conclusion: The test results show that pure zinc stearate and pure calcium stearate exhibit a single and clear thermal melting behavior in the ranges of approximately 121.7℃ to 127.3℃ and approximately 152.1℃ to 156.8℃, respectively.
[0066] During the heating process, the sequential thermal energy buffer system clearly exhibited two completely separate melting ranges. Its first melting range (121.1-126.5℃) corresponds closely to the melting range of pure zinc stearate, while its second melting range (151.7-156.1℃) corresponds closely to the melting range of pure calcium stearate.
[0067] This data confirms that the two metal stearates maintained their independent thermal response characteristics in the mixed system and did not form a eutectic. Based on fundamental principles of physicochemical science, melting is a typical endothermic phase transition process that absorbs a significant amount of latent heat. Therefore, the observation of two independent melting events occurring sequentially at different temperatures provides direct experimental evidence for a sequential thermal buffering mechanism: when the ambient temperature rises, zinc stearate first melts and absorbs heat in the lower temperature range, forming the first-level thermal buffer; if the temperature continues to rise, calcium stearate continues to melt and absorb heat in the higher temperature range, forming the second-level thermal buffer. This stepped energy absorption pattern verifies the technical concept of this invention—using component blending to achieve sequential management of heat flow.
[0068] Test Example 2: This test case aims to evaluate the macroscopic physical and mechanical properties of the friction pads prepared in the various embodiments and comparative examples, including hardness, impact strength, and compressive strength.
[0069] Experimental methods: Each group of samples was tested according to national standards. All samples were conditioned for at least 24 hours in a standard laboratory environment (temperature 23±2℃, relative humidity 50±5%) before testing. Five valid samples were prepared for each performance test, and the test results were taken as their arithmetic mean.
[0070] Rockwell hardness: Determined using a Rockwell hardness tester according to GB / T3398.2-2008 standard. HRM scale was used, with a test force of 980.7 N, a steel ball indenter diameter of 12.7 mm, and a loading time of 15 s. Measurements were taken at five different locations on each sample.
[0071] Impact strength: According to GB / T1043.1-2008 standard, the unnotched specimen (size 80mm×10mm×4mm) was tested using a cantilever beam impact testing machine.
[0072] Compressive strength: Determined using a universal testing machine according to GB / T1041-2008 standard. The sample size was 10mm×10mm×4mm, and the loading speed was 2mm / min until the sample failed. The maximum compressive stress was recorded.
[0073] Experimental data: The basic physical and mechanical performance test data of each embodiment and comparative example are shown in Table 2.
[0074] Table 2. Basic physical and mechanical performance test data of each embodiment and comparative example
[0075] Conclusion: The data in Table 2 show that the samples of Examples 1-4 are significantly better than all the comparative samples in terms of Rockwell hardness, impact strength and compressive strength.
[0076] Comparing Example 1 with Comparative Examples 1 and 2, it is evident that a high-performance cyanate ester resin matrix is fundamental to achieving excellent mechanical properties, but it is not the sole determining factor. Comparative Example 3, using the same matrix and hybrid reinforcing fiber system as Example 1, but excluding the sequential thermal buffer system and catalytic in-situ film-forming system, exhibited a significant decrease in all its mechanical properties. This indicates that the catalytic in-situ film-forming system (antimony trioxide, silica, attapulgite clay) plays an effective microscopic reinforcing role in the material. Uniformly dispersed within the matrix, it effectively transfers loads, inhibits the propagation of microcracks, and thus improves the overall strength and toughness of the composite material.
[0077] Further comparison of Example 1 with Comparative Examples 5 and 6 reveals that the introduction of acid-treated attapulgite clay significantly enhances the mechanical properties of the material. This is attributed to the fact that acid treatment improves the interfacial compatibility between the attapulgite clay and the resin matrix, allowing it to more effectively exert its nanorod-like structure's reinforcing and pinning effect on the matrix. In summary, this invention constructs a friction material with excellent comprehensive physical and mechanical properties through the synergistic effect of a high-performance matrix, hybrid fibers, and functional micro / nano fillers.
[0078] Test Example 3: This test case aims to evaluate the stability of the friction coefficient, wear resistance, and resistance to thermal fading and recovery of various friction pads under high-temperature conditions.
[0079] Experimental methods: The MM-1000 friction and wear testing machine was used for testing in pin-disc contact mode. Each set of samples was machined into pin specimens with dimensions of 10mm × 10mm × 10mm. The mating disk was made of 45# steel (hardness 45-50 HRC) with a surface roughness Ra = 0.4 ± 0.1 μm. Before testing, all specimens and mating disks were ultrasonically cleaned with acetone and dried.
[0080] The testing program consists of three phases: Friction coefficient-temperature test: Under a contact pressure of 1 MPa and a rotation speed of 400 rpm, the friction interface temperature was raised from 50℃ to 450℃ at a rate of 5 K / min using an external heating device for the mating disc, and the change of friction coefficient with temperature was continuously recorded.
[0081] Constant temperature wear test: The test was conducted continuously for 2 hours under constant temperature of 300℃, contact pressure of 1MPa, and rotation speed of 400rpm. The mass loss of the pin sample was accurately measured before and after the test, and its volumetric wear rate was calculated based on the material density.
[0082] Fade-Recovery Test: Reference stage: Friction was performed at 100℃ for 10 minutes under conditions of 1MPa and 400rpm, and the average friction coefficient of the last 2 minutes was recorded as the reference friction coefficient.
[0083] Thermal decay stage (Fade): The temperature is rapidly raised to 400°C, and friction is applied for 15 minutes under these conditions. The average friction coefficient in the last 2 minutes is recorded as the high-temperature friction coefficient.
[0084] Recovery phase: Quickly reduce the temperature back to 100°C, continue friction for 15 minutes under this condition, and record the average friction coefficient of the last 2 minutes as the recovery friction coefficient.
[0085] Calculation principle: Thermal degradation rate (%) = (Base friction coefficient - High-temperature friction coefficient) / Base friction coefficient × 100%; Recovery rate (%) = Recovery friction coefficient / Reference friction coefficient × 100%.
[0086] Experimental data: The high-temperature friction and wear performance test data of each embodiment and comparative example are shown in Table 3.
[0087] Table 3. High-temperature tribological and wear performance test data of each embodiment and comparative example.
[0088] Conclusion: Examples 1-4 all maintained a friction coefficient above 0.40 at 400℃, exhibiting extremely high thermal stability. Their thermal degradation rates were all below 8%, recovery rates were close to 100%, and high-temperature volumetric wear rates were extremely low. This indicates that the present invention can suppress the deterioration of frictional performance caused by high temperatures.
[0089] Comparative Example 1 (traditional phenolic system) showed a significant drop in friction coefficient at high temperatures, with a thermal degradation rate exceeding 70% and a recovery rate of less than 50%, accompanied by severe wear. While Comparative Examples 2 and 3 exhibited improved performance due to the use of cyanate ester matrices, their high-temperature friction coefficients remained lower than the examples, and thermal degradation was still significant. This demonstrates that relying solely on a high-performance matrix cannot solve the problem; the zinc stearate, calcium stearate, antimony trioxide, silica, and surface-treated attapulgite clay added in this invention are key to maintaining high-temperature frictional stability.
[0090] The comparison between Example 1 and Comparative Example 4 demonstrates the necessity of a sequential thermal energy buffering system. Comparative Example 4, lacking calcium stearate, exhibits a significantly higher thermal decay rate (16.7%) than Example 1 (6.8%), indicating that a single thermal buffering mechanism has limited capacity to cope with rapid temperature rises. In contrast, a stepped heat absorption system can more effectively protect the substrate and create conditions for subsequent interfacial film formation reactions.
[0091] The comparison between Example 1 and Comparative Examples 5 and 6 demonstrates the core role of surface-treated attapulgite clay. Comparative Example 5, lacking attapulgite clay, exhibited a volumetric wear rate more than twice that of Example 1, indicating that its high-temperature friction film was not firmly adhered or sufficiently dense. Comparative Example 6, using untreated attapulgite clay, showed better performance than Comparative Example 5, but still inferior to Example 1. This verifies the catalytic activation effect of acid treatment on attapulgite clay, promoting the efficient and stable formation of a protective friction film at high temperatures.
[0092] In summary, through the active thermal regulation and synergistic effect of the sequential thermal energy buffer system and the catalytic in-situ film formation system, a stable high-temperature protective structure was constructed at the friction interface, thereby solving the thermal degradation problem of traditional friction materials.
[0093] Test Example 4: This test case aims to evaluate the abrasiveness of different friction pad materials to metal mating components, in order to assess their protective effect on wire ropes of mine hoists during long-term use.
[0094] Experimental methods: This test directly uses the mating steel disc used after the isothermal wear test in Test Example 3 as the evaluation object. The test sample groups are Example 1, Comparative Example 1, and Comparative Example 3. The test steps are as follows: (1) Remove the mating steel discs that have completed the wear test from the testing machine, clean them with acetone in an ultrasonic cleaner for 5 minutes to remove the wear debris and transfer film attached to the surface, and then dry them in an oven at 60°C for 30 minutes.
[0095] (2) Using an analytical balance with an accuracy of 0.1 mg, measure the mass of the mating steel disc after cleaning and drying, and compare it with the initial mass before the test to calculate its mass loss.
[0096] (3) Using a high-precision surface profilometer, measure the profile curve of the wear track at four different locations evenly distributed on the circumference along the radial direction of the wear track on the paired steel disc. Record the maximum wear track depth at each location and calculate the average value. At the same time, measure the surface roughness (Ra) of the wear track area.
[0097] Experimental data: The wear test data of the paired steel discs of some samples are shown in Table 4.
[0098] Table 4. Wear test data of the mating steel discs for some samples
[0099] Conclusion: The data in Table 4 show that the mass loss, wear track depth and surface roughness of the paired steel discs matched with Example 1 are much lower than those of Comparative Example 1 and Comparative Example 3.
[0100] Comparative Example 1, using a traditional phenolic resin-based material, caused severe wear on the steel disc. This is typically due to its friction mechanism relying on the high contact stress generated at the friction interface by hard abrasive particles, leading to plowing and material removal from the mating surfaces. Although Comparative Example 3 employed a high-performance matrix, the lack of a sequential thermal energy buffer system and a catalytic in-situ film-forming system resulted in relatively direct metal-composite material contact with the steel disc at high temperatures, leading to significant adhesive wear and abrasive wear.
[0101] The sample in Example 1 exhibited excellent protection for the metal mating components, attributed to the sequential thermal buffering system and the catalytic in-situ film formation system. During high-temperature friction, this system generates a dense composite metal salt glassy friction film in situ. This friction film not only covers the pad surface but also partially transfers and firmly adheres to the surface of the mating steel disk, forming a protective interface layer. This transforms the friction from direct contact between the pad substrate and the steel disk into contact between friction films. This interface film effectively isolates direct metal-composite material contact, significantly reducing abrasive wear and adhesion effects, thereby greatly mitigating wear on the mating steel disk.
Claims
1. A friction liner for a mine hoist made of a novel composite material, characterized in that, Made from raw materials comprising the following parts by weight: Matrix resin: 30-45 parts; Blended reinforced fiber system: 35-50 parts; Sequential thermal energy buffering system: 3-8 parts; Catalytic in-situ film formation system: 4-13 parts; Basic friction performance modifier: 4-10 parts; The matrix resin is a bisphenol A cyanate resin.
2. The friction liner for a mine hoist made of the novel composite material according to claim 1, characterized in that, The hybrid reinforcing fiber system is composed of basalt fiber and aramid fiber, wherein the amount of basalt fiber is 26.6-35 parts and the amount of aramid fiber is 8.4-15 parts.
3. The friction liner for a mine hoist made of the novel composite material according to claim 1, characterized in that, The sequential thermal energy buffer system is composed of zinc stearate and calcium stearate, wherein the mass ratio of zinc stearate to calcium stearate is 1:1 to 3:
1.
4. The friction liner for a mine hoist made of the novel composite material according to claim 1, characterized in that, The catalytic in-situ film formation system consists of antimony trioxide, silicon dioxide, and surface-treated attapulgite clay, wherein the average particle size of the antimony trioxide is 0.2–0.8 μm, and the average particle size of the silicon dioxide is 10–50 nm.
5. The friction liner for a mine hoist made of the novel composite material according to claim 4, characterized in that, The particle size of the acid-treated attapulgite clay is no greater than 38 μm.
6. A manufacturing process for friction linings for mine hoists made of novel composite materials, used to prepare friction linings for mine hoists made of the novel composite materials as described in any one of claims 1-5, characterized in that, Includes the following steps: (a) The components of the catalytic in-situ film formation system are dispersed in the solvent of bisphenol A cyanate resin to form a functional suspension; (b) The components of the sequential thermal energy buffer system are mixed with the components of the basic friction performance modifier to obtain low-temperature functional powder; (c) The components of the hybrid reinforcing fiber system are impregnated in the functional suspension and fully wetted, and then pre-dried to obtain a resin prepreg; (d) The resin prepreg is stacked and the low-temperature functional powder is spread between the layers to obtain a blank; (e) The blank is subjected to programmed heating and curing to obtain a friction pad.
7. The production process of the friction liner for a mine hoist made of a novel composite material according to claim 6, characterized in that, Prior to step (a), the method also includes the step of preparing surface-acid-treated attapulgite clay: Add attapulgite clay powder to a sulfuric acid solution with a concentration of 2-5 mol / L, stir and react at 80-95℃ for 2-6 hours, and then filter, wash and dry.
8. The production process of the friction liner for a mine hoist made of a novel composite material according to claim 6, characterized in that, The specific method of step (d) is as follows: The resin prepreg is cut and layered. Between every two layers of prepreg, a layer of the low-temperature functional powder is evenly spread using an electrostatic or vibrating sieve device, with a spreading amount of 50-150 g / m³. 2 .
9. The production process of the friction liner for a mine hoist made of a novel composite material according to claim 6, characterized in that, In step (e), the process parameters for the programmed temperature rise curing molding are as follows: First, heat the billet to 80-100℃ under a pressure of 0.5-1.5MPa and hold for 45-75 minutes; then increase the pressure to 10-20MPa and heat to 180-200℃ at a rate of 1-3℃ / min, and hold for 90-150 minutes.
10. The production process of the friction liner for a mine hoist made of a novel composite material according to claim 6, characterized in that, Following step (e), a high-temperature post-treatment step is also included: After demolding, keep the product at 215-230℃ for 120-240 minutes.